Linguophilosophical principles of modern religious discourse - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The specificity of linguophilosophical principles of modern religious discourse is found. The tendencies of the language of religion are studied through the prism of social and cultural factors.